2009
DOI: 10.1152/ajpregu.90555.2008
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin modulates electrical activity of area postrema neurons

Abstract: Ghrelin, a peptide hormone secreted from the stomach, is known to have a potent appetite-stimulating activity. Recently, it has been shown that area postrema (AP), a caudal brain stem center that lacks a blood-brain barrier, is a key site of activity for ghrelin in stimulating appetite and regulating pancreatic protein secretion. In this study, we have examined the ability of ghrelin to regulate the electrical activity of area postrema neurons using patch-clamp electrophysiology. Using current-clamp configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 70 publications
4
36
0
4
Order By: Relevance
“…PK2 was also shown to influence AP cells in a concentration-dependent manner, with an apparent EC 50 that falls between previously identified EC 50 values for PK2 of 2.3 and 63 pM in the paraventricular nucleus and SFO, respectively (6,48). Similarly, other peptides that have been shown to influence AP neuronal activity have also been reported to exert depolarizing and hyperpolarizing effects on different subpopulations of AP cells (9,10,46,47). Our findings with PK2 indicate that the differential responsiveness of separate populations of AP neurons is most likely associated with the separate roles of these neurons in the regulation of integrated autonomic outputs.…”
Section: Discussionsupporting
confidence: 62%
“…PK2 was also shown to influence AP cells in a concentration-dependent manner, with an apparent EC 50 that falls between previously identified EC 50 values for PK2 of 2.3 and 63 pM in the paraventricular nucleus and SFO, respectively (6,48). Similarly, other peptides that have been shown to influence AP neuronal activity have also been reported to exert depolarizing and hyperpolarizing effects on different subpopulations of AP cells (9,10,46,47). Our findings with PK2 indicate that the differential responsiveness of separate populations of AP neurons is most likely associated with the separate roles of these neurons in the regulation of integrated autonomic outputs.…”
Section: Discussionsupporting
confidence: 62%
“…Rats with lesions in the area postrema, a caudal brain stem center devoid of blood-brain barrier, did not respond to peripheral acyl ghrelin-induced stimulation of food intake (Gilg and Lutz, 2006). A recent patch-clamp electrophysiological study showed that acyl ghrelin exerted a direct effect on electrical activity of neurons in the area postrema, another brain region lacking the blood-brain barrier, supporting the notion that acyl ghrelin could act via the area postrema to regulate feeding and energy homeostasis (Fry and Ferguson, 2009). In addition, electrophysiological recordings found that acyl ghrelin stimulated the activity of arcuate NPY neurons and mimicked the effect of NPY in the paraventricular nucleus of the hypothalamus, revealing that release of acyl ghrelin at the arcuate nucleus and hypothalamic paraventricular nucleus might stimulate the release of orexigenic peptides and neurotransmitters, thus representing a regulatory circuit controlling energy homeostasis (Cowley et al, 2003).…”
Section: Access Of Ghrelin Gene Products To the Central Nervous Smentioning
confidence: 91%
“…Receptor localization has been shown by in situ hybridization in rats, mice, and lemurs (Guan et al, 1997;Mitchell et al, 2001;Zigman et al, 2006;Andrews et al, 2008Andrews et al, , 2009Ferens et al, 2010a,b). Moreover, ghrelin and other specific agonists for ghrelin receptors have direct actions on neurons in the brain and spinal cord (Nakazato et al, 2001;Cowley et al, 2003;Lin et al, 2004;Shimizu et al, 2006;Fry and Ferguson, 2009;Ferens et al, 2010a).…”
mentioning
confidence: 99%